BINDING d-ELEMENT OF THE 4TH PERIOD OF V-GROUP OF THE PERIODIC SYSTEM OF D.I. MENDELEYEV AND ITS PARAMAGNETIC PROPERTIES - Nasirov R.,; Kalauova A.S.,; Kuspanova B.,; Satenov K.G., (Academic Scientific Journal of Chemistry, 2020)
Vanadium is a connecting element between the main subgroup VA and the subgroup VB. In the opinion of B.V. Nekrasov, if we compare the VВ group of vanadium elements with the valence states of P and Аs VА main subgroup, then in the oxidation states of -3, 0, +3 arsenic is an analogue of phosphorus, and in the oxidation state +5, it will not be an analogue of phosphorus. In contrast, in the low oxidation degrees of vanadium, it differs from phosphorus, and in the oxidation state of +5 vanadium is not a complete analogue of phosphorus. The similarity of the electronic configuration of atoms for vanadium and phosphorus in the +5 oxidation state specifies the similarity of the properties of their chemical compounds. When comparing vanadium and its compounds with elements of the VA subgroup, we conclude that vanadium is a binding element between the VA subgroup and the VB subgroup and the compounds have similar properties. As a result of many years of work, it was found that vanadium in the penta- and tetravalent states has paramagnetic properties. In crude oil, it is in a tetravalent state. In order to improve the standard photocalorimetric method for determining vanadium in oil and petroleum ashes, a more rapid method was proposed for estimating the total concentration of vanadium based on the interaction of V2O5 with concentrated hydrochloric acid. Studies of the EPR spectra of porphyrin complexes with transition metals such as copper were of great importance in the identification of natural porphyrin complexes. In the course of comparison of experimental works of paramagnetic properties of vanadium and phosphorus with each other, it can be said that their application is of great practical importance in different fields of science. Summing up the results of studying the reduction of triphenylphosphine with an alkali metal, we proposed a scheme for the splitting of triphenylphosphine, including the formation of radical anions.